Sea Kayaker's More Deep Trouble : More True Stories And Their Lessons From Sea Kayaker Magazine - Cunningham Christoper (Mc Graw Hill Education, 2014)
Read these tales, understand the lessons learned in these incidents, and respect the advice given as you take your next kayaking adventure. This tome of danger and survival may ultimately save your life.